Females and Tax Avoidance: Evidence from the Agency Problem Perspective - Arfian Erma Zudana; Chrismanuel John Abram Tarigan; Reza G. Lopez Hutabarat; Arsy Haikal (Jurnal Reviu Akuntansi dan Keuangan, 2021)
Gender diversity has long been an issue being studied in previous studies. Mostly, they exploit the different characteristics of females and males and how they affect corporate behaviour. However, prior studies largely examine the presence of female in either agent or principal. We fill the research gap by examining the presence of females in both agent and principal on tax avoidance. We examine the relationship between females and tax avoidance using a quantitative research method. Using 538 firm-year observations of Indonesian listed firms during the period 2015 – 2019, we find that female presence is related to a higher degree of tax avoidance. Moreover, we find that the relationship is driven by the presence of females as auditors signing partners. Our result does not reflect the negative side of having females in organizations because we use a broad measure of tax avoidance. Our result may provide insight for shareholders or other related parties to consider an additional factor, namely the presence of females in both agent and principal, to assess companies' tax avoidance behavior.